Midwives' perspectives about using individualized care plans in the provision of immediate postpartum care in Uganda; an exploratory qualitative study - Mariam Namutebi; Gorrette K. Nalwadda; Simon Kasasa; Patience A. Muwanguzi; Dan K. Kaye (BMC, 2023)
Abstract Introduction Individualized care planning has been slowly integrated into practice in Uganda with minimal documentation of how the concept is applied in providing care. This study explored the perceptions of midwives about the use of individualized care plans (ICPs) in the provision of immediate postpartum care. Methods An exploratory descriptive qualitative approach was used in this study. We interviewed fifty midwives from 37 health facilities in Uganda's greater Mpigi region. The midwives, who were certificate and diploma holders, were purposively enrolled in the selected facilities. Deductive content analysis was done based on the COM-B model. Results Four themes emerged from the data namely; compatibility, motivation, opportunities, and the midwives' suggested strategies and targets for improved individualized care planning. The midwives were aware of individualized care planning and they utilized it in their provision of immediate postpartum care especially when assessing clients for risks, preparing clients for referral, caring for Human Immunodeficiency virus (HIV) exposed babies and their mothers, and educating/ supporting first-time mothers (automatic motivation). Having a good nurse-patient relationship, privacy, and ample time to care for the clients were noted as motivators for individualized care plan use, while poor documentation of care, high patient load, and perceived patients' lack of understanding of the complexities of illness in the immediate postpartum period were the barriers (social opportunity) identified by midwives to the use of individualized care planning. Conclusion There are still capability, motivation, and opportunity hindrances to the use of individualized care planning. Staff recruitment, training, and harmonization of the documentation forms may improve the use of care plans in the postpartum period.